PENGEMBANGAN TES DIAGNOSTIK UNTUK MENGIDENTIFIKASI MISKONSEPSI SISWA PADA MATERI USAHA KELAS XI DI SMA PONTIANAK - Arman, Daly; Maria Silitonga, Haratua Tiur; Mahmudah, Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to produce multiple choice diagnostic tests that are used to detect misconceptions of students on the chapter of work in high school. This study used research & development (R & D) method which consists of seven steps, (1) research and information gathering, carried out by looking at previous studies on the chapter of work (2) planning, including determining the tests, compiling test lines, choose the form of the test, and determine the length of the test (3) develop a preliminary form of the product, in the form of test preparation (4) preliminary field trials, involving 15 students (5) revisions based on the results of preliminary field trials, (6) main field tests, involving 72 students from SMAN 3 Pontianak and Santun Untan High School Pontianak (7) revised based on the main field test. The results of the data analysis showed that the diagnostic test was developed based on the initial conception of students in the chapter of work of several previous studies, test validity of 0.70, test reliability of 0.70, test readability index of 6.44, and the difficulty level of 0. 44. Based on the results of the analysis, as many as 16 diagnostic test questions met the characteristics of the test namely the test was developed based on the initial conception of students, high validity, high reliability, readability index in accordance with the level of education of students, and the low difficulty level.Â Keywords: Development, Diagnostic Test, WorkÂ